2021
DOI: 10.3390/ma14123177
|View full text |Cite
|
Sign up to set email alerts
|

Compression and Strain Predictive Models in Non-Structural Recycled Concretes Made from Construction and Demolition Wastes

Abstract: This work aims to investigate different predictive models for estimating the unconfined compressive strength and the maximum peak strain of non-structural recycled concretes made up by ceramic and concrete wastes. The extensive experimental campaign carried out during this research includes granulometric analysis, physical and chemical analysis, and compression tests along with the use of the 3D digital image correlation as a method to estimate the maximum peak strain. The results obtained show that it is poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Furthermore, considering that the concrete was made of recycled aggregates, a coefficient of variation of about 10% was observed for the compressive and indirect tensile strength and around 16.5% was observed for the modulus of elasticity. This value can be considered acceptable for this particular type of concrete given the greater inherent heterogeneity of recycled aggregates when compared to natural aggregates [ 7 ]. Taking into account these results, it can be stated that the concrete can be used for structural purposes, which is classified as HA-30.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, considering that the concrete was made of recycled aggregates, a coefficient of variation of about 10% was observed for the compressive and indirect tensile strength and around 16.5% was observed for the modulus of elasticity. This value can be considered acceptable for this particular type of concrete given the greater inherent heterogeneity of recycled aggregates when compared to natural aggregates [ 7 ]. Taking into account these results, it can be stated that the concrete can be used for structural purposes, which is classified as HA-30.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, the use of recycled concrete has garnered substantial attention across different applications. Given the nature of these compounds, it is essential to know their mechanical properties and limitations in order to determine their suitability in line with specific sample composition [ 5 , 6 , 7 ]. Among the different types of recycled aggregates, prior studies [ 8 , 9 ] have demonstrated the viability of precast concrete in the manufacture of structural elements, providing a sustainable alternative with an adequate performance.…”
Section: Introductionmentioning
confidence: 99%
“…To prepare the concrete, the compressive strength class had to first be chosen from which the minimum w/c ratio to use was deduced. Then the optimal particle size curve was determined, obtained using a predetermined theoretical curve as a reference (Bolomey’s curve) [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…This technique can be used for flat specimens in its two-dimensional approach and for specimens with greater curvature through its three-dimensional approach [28]. In particular, the 2D approach employed in this study has been used to obtain the strains and to monitor damage progression [29] in works on materials with similar heterogeneous behaviour, including earth-derived aggregates such as sustainable concretes [30] and cementitious materials that incorporate fibres [31]. Nevertheless, it is a novel technique in the field of earthen materials, and there are few studies of its application due to the sample preparation requirements, although it has proved to be a promising technique for obtaining full-field strains and cracks [32].…”
Section: Introductionmentioning
confidence: 99%